Mapping the knowledge domain of financial decision making: A scientometric and bibliometric study - Guo, Lin; Cheng, Junlong; Zhang, Zhishuo (Frontiers in Psychology, 2022)
Based on a 12-year bibliographic record collected from the Web of Science (Thomson Reuters) database, the present study aims to provide a macroscopic overview of the knowledge domain in financial decision making (FDM). A scientometric and bibliometric analysis was conducted on the literature published in the field from 2010 to 2021, using the CiteSpace software. The analysis focuses on the co-occurring categories, the geographic distributions, the vital references, the distribution of topics, as well as the research fronts and emerging trends of financial decision making. The steady increase of papers published year by year demonstrates the increasing interest on this topic at the international level. The scientometric analysis of the literature showed that financial decision, investment decision, and financing decision stand out of the crowd of research on FDM, suggesting their important role for FDM and its research. The analysis of citation burst analysis predicted the focus of topics, i.e., the impact of individual differences such as financial literacy, gender and age on FDM in the coming years. Different from the traditional approach of literature review, this bibliometric analysis offers a scientometric approach to reveal the status-quo and the development trend of FDM by micro and quantitative means. In addition, future research directions for the field are recommended.